KAJIAN NOVEL BAIT-BAIT MULTAZAM KARYA ABIDAH EL KHALIEQY DENGAN PENDEKATAN SEMIOTIKA ROLAND BARTHES - Rina Octaviani; Widowati Widowati (Universitas Sarjanawiyata Tamansiswa, 2016)
The purpose of this study is as follows. (1) Describe the distribution and amount leksia in the novel Bait-Bait Multazam Abidah El Khalieqy work. (2) Describe the codes in the novel Bait-Bait Multazam Abidah El Khalieqy work. (3) Describe the meaning of the codes in the novel Bait-Bait MultazamAbidah El Khalieqy work. (4) Describing the moral values Bait Bait Multazam Abidah El Khalieqy work. This research is a qualitative research. This study describes the meaning of the code in the novel-Bait Bait Multazam based semiotic Roland Barthes. This research data in the form of units of the events that are relevant to the issues examined. The data source of this research is novel Bait-Bait Multazam. This study researcher used the instrument itself is already equipped semiotic Roland Barthes. Methods of data collection research using formal methods, by reading the entire novel. This research data collection techniques is a technique to read and record. Data analysis method used is a qualitative method. Data analysis techniques using a qualitative descriptive technique which is based on Roland Barthes semiotic approach. Roland Barthes semiotic research results in Bait-Bait Multazam Abidah El Khalieqy works is as follows. (1) Beheading novel Bait-Bait Multazam obtained 55 leksia each leksia bring the codes. (2) Each leksia bring up the code that has to mean, the code is a code action or proairetic (AKS), code hermeneutic (HER), cultural code or referential (REF), code semik (SEM), and the symbolic code (SIM) , (3) The meaning of the code- novel Bait Bait Multazam based language code, the code of literary and cultural code. Code-language novel Bait Bait Multazam concerning the use of Indonesian in the form of Arabic. The Cultural code in the novel Bait-Bait Multazam are their rules in an Arab country. Code literary novel-Bait Bait Multazam is the imagination of author give an appreciation of a convert. (4) Novel-Bait Bait Multazam raises moral values such exemplary faith and devotion, confidence, equality, honesty, and sincerity.